Path Analysis of HDI Mediating Poverty and Unemployment Effects on Economic Growth in Indonesia - Hasibuan, Andriansyah; Nasution, Kautsar Fatin Dharmawan; Fadiya, Feny; Pratiwi, Audina; Silaban, Putri Sari Margaret Julianty (Jurnal Ekonomi Balance, 2025)
Economic growth remains a central goal in Indonesia's development agenda, yet it is often hindered by persistent poverty and unemployment. This study investigates the mediating role of the Human Development Index (HDI) in the relationship between poverty, unemployment, and economic growth across 11 provinces in Indonesia during the 2014–2023 period. Using a quantitative approach and panel data analysis, the study employs path analysis to examine both direct and indirect effects. The results indicate that poverty significantly reduces HDI, and HDI significantly mediates the effect of poverty on economic growth. However, HDI does not significantly mediate the relationship between unemployment and economic growth. The Fixed Effect Model (FEM) was selected as the most appropriate model based on Chow, Hausman, and Lagrange Multiplier tests. The Sobel test confirms the significant mediating role of HDI in the poverty–growth pathway, but not in the unemployment–growth linkage. These findings underscore the importance of enhancing human development as a strategic policy tool to mitigate the negative impacts of poverty on growth. Conversely, the lack of mediation in the unemployment pathway suggests the need for direct employment generation programs. This study contributes to the literature by highlighting the nuanced role of HDI in regional development and offers practical implications for policymakers in aligning social and economic priorities.